Drug interactions with sunitinib. (February 2015) - Bilbao-Meseguer, Idoia; Jose, Begoña San; Lopez-Gimenez, Leocadio R; Gil, Maria A; Serrano, Laura; Castaño, Mikel; Sautua, Saioa; Basagoiti, Amaya De; Belaustegui, Ainhoa; Baza, Beatriz; Baskaran, Zuriñe; Bustinza, Alazne
Purpose: Sunitinib is a tyrosine kinase inhibitor indicated for the treatment of gastrointestinal stromal tumor, advanced renal cell carcinoma, and pancreatic neuroendocrine tumors. The aim of this article is to describe the pharmacological interactions between sunitinib and commonly prescribed drugs. Method: We reviewed available information on pharmacological interactions between sunitinib and concomitantly prescribed drugs. Drugs were grouped into different therapeutic groups according to the Anatomical Therapeutic Chemical (ATC) classification. Results: Sunitinib interacts with CYP3A4 inducers or inhibitors and with P-glycoprotein and ABCG2 substrates. Pharmacodynamic interactions with drugs have also been found. Conclusion: Current information on drug interactions between sunitinib and other drugs is scarce and most of the times it is difficult to apply to clinical practice. Even so, this difficulty in managing drug interactions should not be a reason to ignore them as they can help to explain intolerances and treatment failures.